The Influence of Principal Leadership, Educational Climate, and Guidance and Counseling Programs on the Incidence of Bullying Among Students in Public Senior High Schools In Manado City - Rinna Y. Kasenda; Joulanda A. M. Rawis; Harol R. Lumapow; Tellma M. Tiwa (Peneliti.net, 2026)
Bullying in senior high schools is a serious issue in educational management because it affects students’ psychological safety, emotional well-being, and the effectiveness of the learning process. School principals are expected to play a key role in creating a safe, inclusive, and non-violent school environment. However, the extent to which principal leadership directly influences student bullying behavior has not been strongly supported by empirical evidence, especially in public high schools. Therefore, this study examines the effect of principal leadership on bullying behavior among students in public senior high schools in Manado City. This research used a quantitative approach with an explanatory survey design. The population consisted of all students in public senior high schools in Manado City, and 385 respondents were selected using the Lemeshow sampling formula. Data were collected through Likert-scale questionnaires measuring perceptions of principal leadership and bullying behavior. The data were analyzed using Structural Equation Modeling (SEM) with AMOS software, including validity, reliability, model fit, and path analysis tests. The results indicate that principal leadership does not have a direct and significant effect on students’ bullying behavior. This suggests that principal leadership operates more indirectly through school policies, management systems, and institutional structures rather than through direct interaction with students. Bullying behavior is found to be more strongly influenced by peer relationships, school climate, and daily social interactions within the school environment. In conclusion, the relationship between principal leadership and bullying behavior is complex and indirect. Therefore, efforts to reduce bullying should not rely solely on leadership but must also involve strengthening school culture, improving peer relationships, and implementing comprehensive anti-bullying strategies that support students’ social and emotional development.